Theatre Strikes Back in the Digital Era: An Interview with Stephan Wolfert - Pennacchia, Maddalena (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
In this edited interview, Stephan Wolfert, American actor and playwright, talks about his pluri-awarded play, Cry Havoc, a one-man show he has been performing since 2012 with several variations through the years; the play is autobiographical but it is also the exemplary story of many US veterans who cannot find a way to readjust to civilian rules once they come back home. The play tells of Wolfert’s struggle with Shakespeare’s words in order to find his own voice to speak what could not be said differently: his own trauma. By bringing to the fore a number of veterans in Shakespeare’s plays, starting from Richard III to Hotspur, Henry V, Coriolanus and many others, Wolfert fascinatingly lights up corners of the Shakespearean macro-text which we knew were there without really seeing them. Wolfert’s approach, in his show as well as in the use of Shakespeare within the DE-CRUIT Veterans Programme he founded, highlights the importance of human interaction through the mediation of the most ancient among media: theatre. Shakespeare’s writing for the theatre, with its characteristic intermedial quality (as it is suspended between page and stage) and cross-cultural inclination (as it has travelled the world), reactivates a holistic sense of the body and, in so doing, it channels powerful and deep physical emotions that can be expressed and shared with mutual benefit by actors and audience alike within the safe communication environment of theatre. Wolfert’s work makes the most of all this and even puts Shakespeare’s language to a therapeutic use for US veterans.